Limits of peripheral acuity and implications for VR system design. Issue 8 (9th August 2018) - Hoffman, David; Meraz, Zoe; Turner, Eric
Abstract: At different retinal locations, we measured the visual system's sensitivity to a number of artifacts that can be introduced in near‐eye display systems. One study examined the threshold level of downsampling that an image can sustain at different positions in the retina and found that temporally stable approaches, both blurred and aliased, were much less noticeable than temporally volatile approaches. Also, boundaries between zones of different resolution had low visibility in the periphery. We also examined the minimum duration needed for the visual system to detect a low‐resolution region in an actively tracked system and found that low‐resolution images presented for less than 40 ms before being replaced with a high‐resolution image are unlikely to be visibly degraded. We also found that the visual system shows a rapid falloff in its ability to detect chromatic aberration in the periphery. These findings can inform the design on high performance and computationally efficient near‐eye display systems. Abstract : We quantify the sensitivity of the visual system to downsampling artifacts in different parts of the retina. These measurements are highly relevant to designing foveated rendering solutions for virtual reality imagery that match the ability of the visual system to detect the impairments. The types of artifacts include different levels of temporal volatility, spatial aliasing, blur, transition boundaries, chromatic aberration, and latency.